PENERAPAN METODE K-MEANS CLUSTERING UNTUK ANALISA BARANG TERLARIS DI DEPO BANGUNAN JAKARTA - Lubis, Baginda Oloan; Salim, Agus; Fibriany, Firstianty Wahyuhening; Sidauruk, Juniato; Suharjanti, Suharjanti (Universitas Lancang Kuning, 2025)
Information systems are developing rapidly due to the increasing need for information, which also results in the growth of large amounts of data. However, it is important that this data can be processed into quality information that is useful to users. Depo Bangunan Jakarta, which specializes in selling various types of hand, power, machine, and accessory tools, faces this challenge. With various types and sizes of goods, Depo Bangunan Jakarta must manage its stock well to avoid wastage in procurement. Data mining is a solution for business people to increase their company's sales. The method used in data mining includes K-Means Clustering, which classifies data into several groups based on their similar characteristics. With this clustering, it is expected that businesses can identify the right marketing strategy for their consumers. The results showed that items such as 4